2019
DOI: 10.1007/s10479-019-03271-6
|View full text |Cite
|
Sign up to set email alerts
|

A centralised DEA approach to resource reallocation in Spanish airports

Abstract: A centralized data envelopment analysis (DEA) approach optimises the resource usage for all the different units in an organization rather than for each unit separately (conventional DEA). This is particularly relevant for the Spanish airports controlled centrally by the Spanish Airport Authority (AENA) rather than by individual airport managers. In this study, a non-oriented Slack-based inefficiency (SBI) DEA model is used in order to reallocate two transferrable inputs (namely, labour costs and operating cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 63 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…The centralised management affects the flexibility of airports to operate, impairing the market attractiveness to airlines, thus, passengers. Recent studies confirm cargo specialisation improves overall system efficiency (Ripoll-Zarraga and Lozano, 2019). Ripoll-Zarraga and Raya (2020) analysed the Spanish airports differing between touristic versus non-touristic cities assuming that national and international visitors travel by air mode, which is unlikely for national tourists.…”
Section: Airports' Investments: Sources Of Inefficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The centralised management affects the flexibility of airports to operate, impairing the market attractiveness to airlines, thus, passengers. Recent studies confirm cargo specialisation improves overall system efficiency (Ripoll-Zarraga and Lozano, 2019). Ripoll-Zarraga and Raya (2020) analysed the Spanish airports differing between touristic versus non-touristic cities assuming that national and international visitors travel by air mode, which is unlikely for national tourists.…”
Section: Airports' Investments: Sources Of Inefficiencymentioning
confidence: 99%
“…, 2009) and cargo (Coto-Millán et al. , 2016; Ripoll-Zarraga and Lozano, 2019). Few studies address other factors explaining efficiency, for example, outsourcing activities (Tovar and Martin-Cejas, 2009), low-cost carrier (LCC) (Coto-Millán et al.…”
Section: Introductionmentioning
confidence: 99%
“…Network DEA models have also been used in assessment of higher education institutions, from different point of views. See for example Yang et al [36] who presented a general two-stage network for assessing 64 Chinese research universities and their evolution over the period of 2010-2013. Hosseini et al [24] analyzed the regress and progress of educational performance of some universities by applying a general network DEA approach with stochastic data.…”
Section: Empirical Applicationmentioning
confidence: 99%
“…Recently, Song et al [37] applied a DEA-based approach to consider production technology heterogeneity among DMUs, allocating a natural resource reduction amount to each DMU. Ripoll-Zarraga and Lozano [36] used a non-oriented slack-based inefficiency DEA model in order to reallocate two transferrable inputs (namely, labour costs and operating costs) between the different airports.…”
Section: Introductionmentioning
confidence: 99%
“…Ripoll Zarraga and Lozano (2019) utilized a non‐oriented Slack‐based inefficiency DEA approach to reallocate two different inputs as labor costs and operating costs in between the airports. This study revealed the strategy to increase the total number of passengers, Cargo and number of aircraft movements while keeping the inputs at the same level with reallocating the inputs in an efficient approach.…”
Section: Data Envelopment Analysis and Airportsmentioning
confidence: 99%